Decoupling of carbon emissions from agricultural land utilisation from economic growth in China - Min Zhou; Bixia Hu (Agricultural Economics (AGRICECON), 2020)
China, as a populous and agricultural country, is confronted with a tremendous challenge involving the balance between agricultural economic growth and carbon emissions from agricultural land utilisation (CEALU). This study calculates the total CEALU in the 31 provinces of mainland China and uses the Tapio model to analyse the decoupling of CEALU from economic growth during the period 2000-2017. The results are shown as follows: (i) The CEALU in China has substantially increased, and there are obvious spatial discrepancies in CEALU from the regional and provincial perspectives. (ii) The decoupling of CEALU from economic growth at the national level shows a progressive improvement. The decoupling trends show significant spatial disparities at the regional level due to different natural and economic conditions. (iii) There is an increase in the numbers of provinces, which have achieved economic growth with the reduction of CEALU. Policymakers should attach more importance to the relationship between CEALU and economic growth, and relevant policies should be adapted to local natural and economic conditions.